Functional Analysis of Epstein-Barr Virus SM Protein: Identification of Amino Acids Essential for Structure, Transactivation, Splicing Inhibition, and Virion Production - Ruvolo, Vivian (American Society for Microbiology, 2004)
The Epstein-Barr virus (EBV) SM protein is a posttranscriptional regulator of cellular and viral gene expression that binds and stabilizes target mRNAs and shuttles from nucleus to cytoplasm. SM enhances expression of several EBV genes required for lytic replication and is essential for virion production. SM increases accumulation of specific mRNAs but also inhibits expression of several intron-containing transcripts. The mechanism by which SM inhibits gene expression is poorly understood. The experiments described here had several aims: to determine whether specific domains of SM were responsible for activation or inhibition function; whether these functions could be separated; and whether one or more of these functions were essential for virion production. A mutational analysis of SM was performed, focusing on amino acids in SM that are evolutionarily conserved among SM homologs in other herpesviruses. Mutation of the carboxy-terminal region of SM revealed a region that is likely to be structurally important for SM protein conformation. In addition, several amino acids were identified that are critical for activation and inhibition function. A specific mutation of a highly conserved cysteine residue revealed that it was essential for gene inhibition but not for transactivation, indicating that these two functions operate through independent mechanisms. Furthermore, the ability of wild-type SM and the inability of the mutant to inhibit gene expression were shown to correlate with the ability to inhibit splicing of a human target gene and thereby prevent accumulation of its processed mRNA. Surprisingly, some mutations which preserved both activation and inhibition functions in vitro nevertheless abolished virion production, suggesting that other SM functions or protein-protein interactions are also required for lytic replication.